Impaired Cardiac Sympathetic Activity Is Associated With Myocardial Remodeling and Established Biomarkers of Heart Failure - Luis M. da Silva; Andréa Coy‐Canguçu; Layde R. Paim; Adriana A. Bau; Camila Nicolela Geraldo Martins; Stephan Pinheiro; Vinicius Citeli Ribeiro; Walter E. Magalhães Rocha; Jose R. Mattos‐Souza; Roberto Schreiber; Lígia Antunes‐Correa; Andrei Sposito; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background 123Iodine‐meta‐iodobenzylguanidine scintigraphy is useful for assessing cardiac autonomic dysfunction and predict outcomes in heart failure (HF). The relationship of cardiac sympathetic function with myocardial remodeling and diffuse fibrosis remains largely unknown. We aimed to evaluate the cardiac sympathetic function of patients with HF and its relation with myocardial remodeling and exercise capacity. Methods and Results Prospectively enrolled patients with HF (New York Heart Association class II–III) were stratified into HF with preserved left ventricular ejection fraction [LVEF] ≥45%) and reduced LVEF. Ventricular morphology/function and myocardial extracellular volume (ECV) fraction were quantified by cardiovascular magnetic resonance, global longitudinal strain by echocardiography, cardiac sympathetic function by heart‐to‐mediastinum ratio from 123iodine‐meta‐iodobenzylguanidine scintigraphy. All participants underwent cardiopulmonary exercise testing. The cohort included 33 patients with HF with preserved LVEF (LVEF, 60±10%; NT‐proBNP [N‐terminal pro‐B‐type natriuretic peptide], 248 [interquartile range, 79–574] pg/dL), 28 with HF with reduced LVEF (LVEF, 30±9%; NT‐proBNP, 743 [interquartile range, 250–2054] pg/dL) and 20 controls (LVEF, 65±5%; NT‐proBNP, 40 [interquartile range, 19–50] pg/dL). Delayed (4 hours) 123iodine‐meta‐iodobenzylguanidine heart‐to‐mediastinum ratio was lower in HF with preserved LVEF (1.59±0.25) and HF with reduced LVEF (1.45±0.16) versus controls (1.92±0.24; P<0.001), and correlated negatively with diffuse fibrosis assessed by ECV (R=−0.34, P<0.01). ECV in segments without LGE was increased in HF with preserved ejection fraction (0.32±0.05%) and HF with reduced left ventricular ejection fraction (0.31±0.04%) versus controls (0.28±0.04, P<0.05) and was associated with the age‐ and sex‐adjusted maximum oxygen consumption (peak oxygen consumption); (R=−0.41, P<0.01). Preliminary analysis indicates that cardiac sympathetic function might potentially act as a mediator in the association between ECV and NT‐proBNP levels. Conclusions Abnormally low cardiac sympathetic function in patients with HF with reduced and preserved LVEF is associated with extracellular volume expansion and decreased cardiopulmonary functional capacity.